The effect of protected soybean meal as a protein supplement on blood metabolites of lactating dairy cows - Henny Leondro; Budi Prasetyo Widyobroto; Adiarto Adiarto; Ali Agus (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
The objective of this study was to determine the effect of undegradable dietary protein (UDP) using protected soybean meal supplementation on blood metabolites of lactating dairy cows. Eighteen early lactating Friesian Holstein cows of 1 to 3 years old were used in this study and observed twelve weeks. All cows received forage and concentrate in a ratio of 62:38 (DM basis). Adaptation to the diet was conducted for 4 weeks. The  cows were divided into 3 groups with different dietary treatments: control diet without UDP and mineral mix (T0), control diet + UDP 40 g/L milk + mineral mix (T1), and  control diet + UDP 60 g/L milk + mineral mix (T2). Fresh water was also offered ad libitum in the pen. In the days 14 and 7 pre-treatment, and in the days 1, 7, 14 and 21 post-treatment, cows were weighted and their blood were collected for chemical analysis. Means between treatments were analyzed using one-way analysis of variance (ANOVA). The results obtained from this study revealed that blood metabolites pattern of lactating cows before and after UDP supplementation subjects to considerable varia-tions. The UDP supplementation had a significant effect on the concentration of Ca. For comprehensive assessment of the effect of UDP supplementation on blood metabolites at different stages of parturient period, further detailed studies should be performed